Stability analysis, chaos control of a fractional order chaotic chemical reactor system and its function projective synchronization with parametric uncertainties - Yadav V.K.; Das S.; Bhadauria B.S.; Singh A.K.; Srivastava M. (My University, 2025)
In this article, the stability analysis, chaos control and function projective synchronization between a fractional order chaotic chemical reactor system and a chaotic chemical reactor system with uncertain parameters are performed with the help of a new lemma for the Caputo derivative and the Lyapunov stability theory. Furthermore, when the parameters of the system are fixed, the lowest order for chaos to exist is determined. The nonlinear control method is used to achieve function projective synchronization and chaos control of considered chaotic chemical reactor system. Numerical simulations are carried out using the Adams-Bashforth Moulton method and the results are depicted through graphs. © 2017 The Physical Society of the Republic of China (Taiwan)